PENGARUH PENGENDALIAN INTERNAL BISNIS ONLINE TERHADAP PENCEGAHAN FRAUD - Febriyanti Pungkasih Rahadi; Sri Sasmita (Jurnal Akuntansi UMMI, 2021)
The development of online business in Indonesia is very fast. The rapid development of this online business cannot be separated from the development of internet technology in Indonesia. However, this does not guarantee that all online businesses have implemented effective and efficient internal controls in their business. To deal with the problem of online business fraud fraud, proper monitoring is needed within the online business internally The purpose of writing this journal is to be able to find out online business information and to find out the effect of online business internal control on fraud prevention and detection in the development of the world economy in Indonesia, especially in the field of online business. In preparing this journal, using descriptive qualitative methods using analysis, data, and utilizing existing theories as supporting materials. This journal uses secondary data sources obtained from other research journals and is based on the "Experian Global Fraud and Identity Report APAC" issued in May 2019. In preparing the journal, the author uses documentation data collection techniques from journals, books and related reports. The report "Experian Global Fraud and Identity Report APAC" issued in May 2019, explained that 40 percent of businesses in Indonesia experienced an increase in losses related to online fraud over the past 12 months. The majority of customers (77 percent) rated 'safety' as the most important element of their online experience. To prevent fraud, it starts with internal control in the online business by authenticating identity, checking, or detecting fraud. Internal control is a way to direct, monitor and measure the level of quality of human resources within an organization. It plays an important role in preventing and detecting fraud and protecting the organization's tangible resources (such as reputation or intellectual property rights such as trademarks).